Mapping of Tourism Objects by Using a Geographic Information System In Aceh Besar District - Mirza Desfandi; Daska Azis; Ahmad Nubli Gadeng; Dita Ramadani Sunarti (Proceedings of AICS - Social Sciences, 2021)
Information and advertisement of tourism places is essential so that visitors around the world know the lovely place to visit. This study aimed to map the distribution of tourism objects by using a Geographic Information System in Aceh Besar district. To reach this objective, a mapping of the distribution of tourism objects based on their type was carried out; the mapping of natural, cultural, and special interest attractions in Aceh Besar District. A qualitative descriptive method was employed in this study to determine the distribution of natural, cultural, and special interest tourism in Aceh Besar District. The map is used as a media presenter to describe and display the distribution of tourism attraction locations. Tourism object location data is obtained by taking the coordinates of the tourist attraction location using google maps or plotting to tourist sites using a tool in the form of a Global Positioning System (GPS) then superimposing the data onto a base map. From the results of taking coordinates using google maps, 63 coordinate points for tourist attraction locations and the remaining four tourism objects cannot be found on google maps. So direct plotting is carried out to take coordinates to tourist attraction locations. Based on the results of the map analysis, it can be concluded that 67 tourism objects were found in Aceh Besar District. The tourism objects are grouped by type; 51 natural attractions, six cultural attractions, and 10 special interest attractions spread over 18 of sub-districts in Aceh Besar district.Keywords: Mapping, Tourism objects, Geographic Information System , Aceh Besar District